Simple Micro-hydro Uses Water as a Renewable Energy Source - Putri, Bunga Meilinda; Ningrum, Listia; Maulida, Nova Masripah (Indonesian Journal of Multidiciplinary Research, 2021)
Fossil fuels are the main source in producing electrical energy continuously on a large scale in various countries. This will have an impact on the exhaustion of fossil fuels. Therefore, energy substitute for fossil fuels is needed. PLTMH is a renewable energy source that uses water to solve the problem of electrical energy. The purpose of this study is to determine the water discharge, the speed of water flow that comes from tap water as a source of electricity generation. Based on research in the journal, the novelty is the manufacture of power plants using simple tools to produce good and accurate research data. The research method used is literature study. Literature studies are taken from various sources that describe power generation tools using energy. From the research results in the journal, it can be seen that the higher the water discharge, the higher the mechanical efficiency of the propeller turbine. In addition, the higher the water discharge also affects the generator output power. The conclusion of this study is that the water flow that is flowed from tap water to the hose greatly affects the voltage generated, where the electric voltage will be greater if the efficiency of the turbine mechanism which acts as a mechanical energy converter and the generator output power as an electrical energy converter is high enough. The impact of the research is expected to continue to be developed and be useful as renewable energy for electrical energy problems.